2012
DOI: 10.5402/2012/528382
|View full text |Cite
|
Sign up to set email alerts
|

Shoelace Wound Closure for the Management of Fracture-Related Fasciotomy Wounds

Abstract: Background. Compartment syndrome is a serious complication that might occur following fractures. The treatment of choice is emergent fasciotomy of all the involved muscle compartments to lower the compartment pressure. The classic management of fasciotomy wounds was split thickness skin graft. Patients and Methods. Seventeen patients with fracture-related compartment syndrome were managed by fasciotomy in the Orthopaedic Casualty Unit of our university hospital. The fractures included four femoral fractures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…(Range3-6). Eid et al [17] carried out similar study and obtained skin closure at an overall average of 4.2 tightening sessions (range 3-7). Ji yong park et al [18] reported 2-6 operations when shoe lace was used as a method of fasciotomy wound closure.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(Range3-6). Eid et al [17] carried out similar study and obtained skin closure at an overall average of 4.2 tightening sessions (range 3-7). Ji yong park et al [18] reported 2-6 operations when shoe lace was used as a method of fasciotomy wound closure.…”
Section: Discussionmentioning
confidence: 92%
“…which otherwise could have happened if closure was attempted in single fashion In our study fasciotomy was performed at an average of 15.2 hrs (range 8-24 hrs) following injury. In a study carried out by EId et al [17] fasciotomy was performed at an average of 21.1 hrs (range 12-36 hrs) following injury. Kakagia et al [20] reported closure time was more if fasciotomy was performed 8hrs after injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Eid et al, closure was obtained at an overall average of 4.2 tightening sessions (range 3-7) whereas, Park et al and Cheng et al reported 2-6 sessions for wound approximation. [21][22][23] Marek et al and Chiverton et al suggested obtaining closure in single sitting. 20,24 We achieved wound approximation in 4 tightening sessions which was on par with other studies in literature.…”
Section: Discussionmentioning
confidence: 99%
“…13 Chiverton et al and Eid et al also utilized suture and catheter for the closure of fasciotomy wounds and got satisfactory results. 14,15 So closure of wounds with soft tissue defects could be done by applying the dermo-traction technique in a better effective way than skin grafting.…”
Section: Discussionmentioning
confidence: 99%